New start of surgical residents training: the first survey of program directors in Korea - Kim, Sung Geun (BMC Med Educ, 2019)
BACKGROUND: The introduction of the 80-h shift restriction for surgical residents in Korea necessitated many changes to their training systems. The purpose of this study was to conduct a survey among program directors, determine the conditions necessary for them to fulfill their responsibilities, and investigate whether there was a difference between tertiary hospitals and general hospitals in the surgical training environment. METHODS: Questionnaires were distributed to program directors nationwide to investigate their status as well as the status, conditions, evaluation methods, and feedback methods of surgical residency training programs. Descriptive statistics and the chi-square test were used for statistical analysis. RESULTS: The response rate was 55% (55/100). These 55 institutes train 71% of all residents and 83.6% of these institutes run surgical skill training programs. A laparoscopic training box was available at 30 (55%) institutes, laparoscopic simulator at 30 (33%), and robotic simulator at only 12 (22%). Internal assessment of residents was conducted at 24 (43.6%) institutes. Regular interviews were conducted with residents at 21 (38.2%) institutes. Regular questionnaires about the training program were conducted among residents at 16 (29.1%) institutes and among training directors at 8 (14.5%). Lastly, 45 (81.8%) program directors reported that at least 30% of their working time was dedicated to residency training. CONCLUSIONS: This is the first study to elucidate current surgical residency training in Korea: Feedback systems for residency assessment and training programs are still lacking, and program directors need to dedicate at least 30% of their time to effectively fulfill their role in residency training.